Multivariate analysis and character association studies for yield and nutritional characters in swarna and type 3 RIL population of rice (Oryza sativa L.) - Shivani, Darmagaru; Neeraja, Cheruvuri Naga; Cheralu, Chandragiri; Shankar, Vuppu Gouri (Journal of Cereal Research, 2021)
The investigation was carried out in one hundred Swarna X Type 3 RIL population of rice to understand the association among yield, yield attributing and nutritional traits. Their direct and indirect effects on the grain yield using correlation and path analysis and the principal component analysis was assessed using multivariate analysis. Significant differences were observed among the RIL population for the traits studied. High values of heritability and genetic advance were observed for plant height, panicle weight, number of filled grains per panicle, panicle weight, 1000-seed weight, grain yield per plant, grain iron and zinc concentration. Character association for the yield attributing traits at both genotypic and phenotypic level revealed significant positive association of grain yield per plant with test weight and plant height. Path coefficient analysis revealed that test weight had highest direct positive effect on grain yield per plant followed by plant height and filled grains per panicle. PCA showed that a cumulative variance of 32.5% from PC1 attributed by grain iron, grain zinc, plant height and test weight would be beneficial in contributing to the total morphological diversity. RILs P45 and P57 have shown higher grain yield per plant with high iron and zinc concentrations. Thus, the trait test weight that showed positive and direct association with grain yield can be focused in selection and can be utilized for improvement in future breeding programmes.